2017
DOI: 10.1093/scan/nsx046
|View full text |Cite
|
Sign up to set email alerts
|

The effect of constraining eye-contact during dynamic emotional face perception—an fMRI study

Abstract: Eye-contact modifies how we perceive emotions and modulates activity in the social brain network. Here, using fMRI, we demonstrate that adding a fixation cross in the eye region of dynamic facial emotional stimuli significantly increases activation in the social brain of healthy, neurotypical participants when compared with activation for the exact same stimuli observed in a free-viewing mode. In addition, using PPI analysis, we show that the degree of amygdala connectivity with the rest of the brain is enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 94 publications
4
25
0
Order By: Relevance
“…Notably, these areas overlapped to a great extent with areas were we have previously demonstrated an eye-contact effect in typical individuals (see Fig. 1 in 38 ). No changes were present in the primary visual cortex, excluding an effect due to arousal and attention alone.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Notably, these areas overlapped to a great extent with areas were we have previously demonstrated an eye-contact effect in typical individuals (see Fig. 1 in 38 ). No changes were present in the primary visual cortex, excluding an effect due to arousal and attention alone.…”
Section: Discussionsupporting
confidence: 51%
“…In the present study, we examined the same group of individuals with autism (plus two additional participants) during the perception of dynamic emotional faces (same stimuli as described in 2 , 38 ) at baseline and after 10 months of open-label bumetanide treatment, specifically examining the effect of bumetanide on amygdala activation. We previously reported the presence of an enhanced eye-contact effect in ASD, demonstrating that forcing them to look in the eyes significantly increased amygdala activation 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that in normally developed individuals, but not those with ASD, attention to the demonstrator’s face was linked to a subsequent reduction of the learned fear response. These findings suggest that individuals with ASD lack the ability to capitalize on facial information in the social context to aid the regulation of anxious responses, providing further clues towards understanding why this population more often suffers from problems with anxiety, and adding to the growing literature investigating learning from observing others [ 13 – 15 , 48 ] and responsiveness to distress in others [ 50 ] in individuals with ASD.…”
Section: Resultsmentioning
confidence: 90%
“…Finally, it is possible that the pattern of reduced social attention during CS+ presentations was caused by enhanced arousal rather than contributing to it. Previous studies have suggested that reduced social attention in ASD may be a means of reducing arousal and should therefore be most likely in high emotional states [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is known from previous studies that gaze to (upright) eyes leads to enhanced activity in brain structures known to be crucial for the face inversion effect as well as in face processing more generally (Hadjikhani et al, 2017;Senju & Johnson, 2009). For example, Hadjikhani et al (2017) demonstrated that the activity in brain regions implicated in the face inversion effect as well as face processing more generally, such as the fusiform face area and amygdala, is enhanced when an individual's gaze is constrained to the eye region. Atypical activation of these areas has previously been documented in SAD (Frick et al, 2013;Gentili et al, 2016).…”
Section: Discussionmentioning
confidence: 99%